A PLUG FLOW-THROUGH REACTOR FOR STUDYING BIOGEOCHEMICAL REACTIONS IN UNDISTURBED AQUATIC SEDIMENTS - Roychoudhury A.N.; Viollier E.; Van Cappellen P. (My University, 1998)
A slow flow, plug-through reactor was developed for measuring equilibrium and kinetic parameters of biogeochemical reactions on intact sections of sediment cores. The experimental approach was designed to preserve the structural, geochemical and microbiological integrity of the sediment sections and, hence, retrieve reaction parameters that apply to in-situ conditions.Inert tracer breakthrough experiments were performed on a variety of unconsolidated surface sediments from lacustrine, estuarine and marine depositional environments. The sediments studied cover wide ranges of composition, porosity (46–83%) and mean grain size (10−4−10−2 cm). Longitudinal dispersion coefficients were determined from the breakthrough curves of Br−. The curves were also used to check for early breakthrough or trailing, that is, features indicative of non-ideal flow conditions. Sediment plugs that exhibited these features were eliminated from further experiments.Dimensionless equilibrium adsorption coefficients (K) of NH4+, were calculated from measured retardation times between the breakthrough of NH4+ and Br−. The values of K at 5°C vary between 0.3 and 2.3, with the highest value obtained in a fine-grained marine sediment, the lowest in a coarse-grained lake sediment. The values for the marine and estuarine sediments agree with values reported in the literature. The dependencies of K on ionic strength (range 0.2-0.7m) and temperature (range 5–25°C) in an estuarine sediment confirm that the main sorption mechanism for NH4+ is ion exchange.The reactor was used in recirculation mode to measure steady-state rates of dissimilatory SO42− reduction in a salt-marsh sediment. Recirculation homogenizes solute concentrations within the reactor, hence facilitating the derivation of reaction rate expressions that depend on solution composition. The rate of microbial S04− reduction was found to be nearly independent of the dissolved SO42− concentration in the range of 2.2−1 mM. Fitting of the experimental rates to a Monod relationship resulted in a maximum estimate of the half-saturation concentration, Ks, of 240 μM. This value is comparable to those reported for a pure culture of SO42−-reducing bacteria, but is significantly smaller than the only other Ks value reported in the literature for SO42− utilization in a natural marine sediment.